Various antioxidant assays of agarwood extracts (Gyrinops versteegii) from West Lombok, West Nusa Tenggara, Indonesia - PRIHANTINI, AMALIA INDAH; RIZQIANI, KANTI DEWI (Society for Indonesian Biodiversity & Universitas Mulawarman, Samarinda, Indonesia, 2019)
Abstract. Prihantini AI, Rizqiani K. 2019. Various antioxidant assays of agarwood extracts (Gyrinops versteegii) from West Lombok, West Nusa Tenggara, Indonesia. Asian J Agric 3: 1-5. However, the species have not been widely explored as a source of natural products in particular antioxidant agents, which protect cells from damage caused by free radicals. The present study was aimed to evaluate antioxidant activities of agarwood extracts from West Nusa Tenggara using various antioxidant assays. The antioxidant activity of leaf, fruit and fruit bark extracts were investigated based on DPPH radicals scavenging activity, reducing power, and β-carotene bleaching assays. The total phenolic content was also investigated. The result showed that leaf extract revealed the strongest antioxidant activity on all assays performed such as DPPH radicals scavenging activity (IC50 22.13±0.71 μg/mL); reducing power (251.85±0.03 mg QE/g dry extract); and β-carotene bleaching activity (IC50 24.23±2.60 μg/mL). The total phenolic content (TPC) in the leaf was higher (184.90±0.76 mg GAE/g dry extract) than fruit bark and bark extracts. The high content of phenolic compounds in G. versteegii leaves indicated that these compounds might contribute to the antioxidant activities. In conclusion, these findings showed that G. versteegii leaves are potential for development as an antioxidant source.